Injection Artesunate has been found to be Superior to Quinine in the Treatment of Severe Malaria in African Children - Faiz, Md Abul (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i2.7727 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):4